A new palatable oral rehydration solution: A randomised controlled cross‐over study in patients with a high output stoma. Issue 1 (5th September 2021) - Culkin, Alison; Gabe, Simon M.; Nightingale, Jeremy M. D.
Abstract: Background: Patients with a jejunostomy or high output stoma may need a glucose–sodium oral rehydration solution drink to maintain hydration. These solutions are unpalatable and a new flavoured pre‐packaged solution was developed. Methods: After 8 h of fasting, 27 patients took 500 mL of the modified World Health Organization (WHO) cholera solution or Glucodrate® (Vitaflo) on two occasions in a cross‐over random order and urine and stomal output was collected for 6 h. Results: There was a small but significant difference in net sodium absorption in favour of the modified WHO cholera solution (10 ± 28 mmol modified WHO cholera solution vs. −1 ± 26 mmol Glucodrate®, p = 0.01). However the Glucodrate® was more palatable, with 24 patients (89%) preferring it to the modified WHO cholera solution ( p < 0.005). Conclusions: Glucodrate® is a more palatable solution than the modified WHO cholera solution and is almost as effective and so can be used when patients find the modified WHO cholera solution unpalatable.